1996
DOI: 10.1097/00000658-199611000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Significant Influence of Accompanying Chronic Hepatitis Status on Recurrence of Hepatocellular Carcinoma after Hepatectomy

Abstract: The results of this study indicated the significant influence of histologic activity of hepatitis on recurrence of HCC. This might support the concept of significant contribution of multicentric hepatocarcinogenesis to recurrence of HCC after hepatectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
94
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(100 citation statements)
references
References 20 publications
5
94
0
1
Order By: Relevance
“…It also must be noted that the histologic status of the noncancerous regions of the liver influence tumor recurrence, especially secondary growths of HCC. 30,[33][34][35] Interestingly, 2 recent articles dealing with the prognosis of patients with HCC have been correlated with physical parameters such as performance status and the presence or absence of symptoms. 36,37 However, we did not compare those classifications in this study, because the physical parameters would have been difficult to determine and organize retrospectively.…”
Section: Discussionmentioning
confidence: 99%
“…It also must be noted that the histologic status of the noncancerous regions of the liver influence tumor recurrence, especially secondary growths of HCC. 30,[33][34][35] Interestingly, 2 recent articles dealing with the prognosis of patients with HCC have been correlated with physical parameters such as performance status and the presence or absence of symptoms. 36,37 However, we did not compare those classifications in this study, because the physical parameters would have been difficult to determine and organize retrospectively.…”
Section: Discussionmentioning
confidence: 99%
“…These patients would receive an unnecessary graft in primary OLT. Although such a low recurrence rate is difficult to obtain in the general population of HCC patients submitted to resection, it can be achieved in selected groups, such as patients with low inflammatory activity 38 and low transaminase values 39 or with the advent of medications that lower the recurrence rate, as shown in a pilot study using retinoids. 40 Cost analysis in our model showed that the cost per additional year offered by the strategy of primary transplantation varied between $25,530 and $92,422 according to the different scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Pathological and genetic analyses have indicated two features in HCC recurrence: multicentric occurrence of new tumours (MO) and intrahepatic metastasis of the original tumour (im) (Tsuda et al, 1992;Matsumoto et al, 2001). It has been reported that MO is significantly influenced by the underlying liver status, such as the presence of active hepatitis (Belghiti et al, 1991;Ko et al, 1996). On the other hand, im is thought to be more closely associated with tumour factors, especially portal vein invasion (vp) (Vauthey et al, 1995;Shimada et al, 1999).…”
mentioning
confidence: 99%